Lipid rafts in the plant plasma membrane? - Bérczi, Alajos; Horváth, György (Acta Biologica Szegediensis, 2003)
In order to study the molecular characteristics of an integral membrane protein, first the protein should be solubilized. Ascorbate-reducible b-type cytochromes are highly hydrophobic integral membrane proteins with six trans-membrane a-helices. A fully ascorbate-reducible b-type cytochrome was easily solubilized by Triton X-100 from phase partition-purified plasma membranes of 5-day-old etiolated bean (Phaseolus vulgaris L.) hooks (Trost et al. 2000). However, under the very same conditions, a similar protein in the phase partition-purified plasma membrane of 9-week-old green Arabidopsis thaliana leaves seemed to be very resistant to solubilization with Triton X-100 (Bérczi et al. 2001). It was assumed that the composition of lipids in the plasma membrane of the two different tissues might influence the solubilization. Results obtained with thin layer chromatography revealed that both quan-titative and qualitative differences exist between the lipid composition of the two plant plasma membranes. The observations are discussed in the light of possible existence of “lipid rafts” in the plant plasma membranes.